Implementing CEDAW to Address Violence against Women and Children in Australia (2023–2024) - Yusrifa, Azzahirah Iffat; Trisnaningtyas, Januari Pratama Nurratri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
Violence against women and children remains a serious social problem in many countries, including Australia. Despite Australia’s formal commitment to the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), gender-based violence continues to occur at alarming rates. This study aims to analyze Australia’s efforts in addressing violence against women and children through the implementation of CEDAW during the period 2023–2024. This research employs a qualitative method using document analysis. The data are obtained from official government reports, policy documents, international conventions, and relevant academic literature related to CEDAW and gender-based violence. The analysis focuses on Australia’s National Plan to End Violence against Women and Children 2022–2032 and its First Action Plan 2023–2027. The findings indicate that Australia demonstrates normative and procedural compliance with CEDAW through policy alignment, institutional mechanisms, and intergovernmental coordination. However, most programs and action plans remain in the implementation or development stage, indicating that substantive outcomes are still limited. Challenges such as cultural norms, data gaps, and coordination between federal and state governments continue to hinder effective implementation. This study concludes that while Australia shows strong commitment to CEDAW principles, sustained implementation and outcome-oriented evaluation are required to effectively reduce violence against women and children.